Thomas Kuhn's `Structure of Scientific Revolutions` applied to exercise science paradigm shifts: example including the Central Governor Model - Pires, F. de O. (British Journal of Sports Medicine, 2013)
According to Thomas Kuhn, the scientific progress of any discipline could be distinguished by a pre-paradigm phase, a normal science phase and a revolution phase. The science advances when a scientific revolution takes place after silent period of normal science and the scientific community moves ahead to a paradigm shift. I suggest there has been a recent change of course in the direction of the exercise science. According to the `current paradigm`, exercise would be probably limited by alterations in either central command or peripheral skeletal muscles, and fatigue would be developed in a task-dependent manner. Instead, the central governor model (GCM) has proposed that all forms of exercise are centrally-regulated, the central nervous system would calculate the metabolic cost required to complete a task in order to avoid catastrophic body failure. Some have criticized the CGM and supported the traditional interpretation, but recently the scientific community appears to have begun an intellectual trajectory to accept this theory. First, the increased number of citations of articles that have supported the CGM could indicate that the community has changed the focus. Second, relevant journals have devoted special editions to promote the debate on subjects challenged by the CGM. Finally, scientists from different fields have recognized mechanisms included in the CGM to understand the exercise limits. Given the importance of the scientific community in demarcating a Kuhnian paradigm shift, I suggest that these three aspects could indicate an increased acceptance of a centrally-regulated effort model, to understand the limits of exercise.